Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ma300410v
|View full text |Cite
|
Sign up to set email alerts
|

RAFT Agent Design and Synthesis

Abstract: This Perspective reviews the design and synthesis of RAFT agents. First, we briefly detail the basic design features that should be considered when selecting a RAFT agent or macro-RAFT agent for a given polymerization and set of reaction conditions. The RAFT agent should be chosen to have an optimal C tr (in most circumstances higher is better) while at the same time it should exhibit minimal likelihood for retarding polymerization or undergoing side reactions. The RAFT agent should also have appropriate solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
516
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(529 citation statements)
references
References 213 publications
7
516
0
6
Order By: Relevance
“…The factors which influence choice of RAFT agent for a particular polymerization has been presented in various reviews. [17][18][19]28,137] The effectiveness of the RAFT agent depends on the monomer being polymerized and is determined by the properties of the free radical leaving group R and the group Z which can be chosen to activate or deactivate the thiocarbonyl double bond of the RAFT agent (1) and modify the stability of the intermediate radicals (2) and (4). For effective RAFT polymerization (Scheme 1, Fig.…”
Section: Chartmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors which influence choice of RAFT agent for a particular polymerization has been presented in various reviews. [17][18][19]28,137] The effectiveness of the RAFT agent depends on the monomer being polymerized and is determined by the properties of the free radical leaving group R and the group Z which can be chosen to activate or deactivate the thiocarbonyl double bond of the RAFT agent (1) and modify the stability of the intermediate radicals (2) and (4). For effective RAFT polymerization (Scheme 1, Fig.…”
Section: Chartmentioning
confidence: 99%
“…include those on the kinetics and mechanism of RAFT polymerization, [26,27] RAFT agent design and synthesis, [28] the use of RAFT to probe the kinetics of radical polymerization, [29] microwaveassisted RAFT polymerization, [30,31] RAFT polymerization in microemulsion, [32] end-group removal/transformation, [33][34][35][36] the use of RAFT in organic synthesis, [37] the combined use of RAFT polymerization and click chemistry, [38] the synthesis of star polymers and other complex architectures, [39][40][41][42] the synergistic use of RAFT polymerization and ATRP, [43,44] the synthesis of self assembling and/or stimuli-responsive polymers, [45][46][47] and the use of RAFT-synthesized polymers in green chemistry, [48] polymer nanocomposites, [49][50][51] drug delivery and bioapplications, [41,46,47,[52][53][54][55][56][57][58][59][60] and applications in cosmetics [61] and optoelectronics. [62] The process is also given substantial coverage in most recent reviews that, in part, relate to polymer synthesis, living or controlled polymerization or novel architectures.…”
Section: Introductionmentioning
confidence: 99%
“…The CTA 5 was then used to polymerise N-vinylpyrrolidone (NVP) in a controlled manner to give PVP chains with alkyne end groups (Supplementary Information, Scheme S3). In the literature [38][39][40][41][42] , both xanthate and dithiocarbamate chain transfer agents were shown to be good candidates for polymerising NVP, a monomer that is a member of the "less activated monomers" (LAM) class described by Keddie et al 43 Furthermore, Patel et al 44 and Akeroyd et al 31 reported the preparation of alkyne-terminated RAFT agents which were used for preparing "macro-RAFT agents" or clickable polymers respectively. The ratio RAFT agent : initiator (AIBN) was optimised to obtain relatively high conversion and good control of the polymerisation, and we found that 1:0.7 was a good compromise, giving a monomer conversion and a Ɖ M of 80% and 1.4 respectively.…”
mentioning
confidence: 99%
“…A sufficiently large number of activation-deactivation cycles are required for low polydispersity [4][5][6][7]. Examples of the capping agent (X) include nitroxides, dithioesters, tellurides, and halogens [8][9][10][11][12][13][14][15]. Halogens are combined with transition metal catalysts [13][14][15].…”
Section: Introductionmentioning
confidence: 99%